2021
DOI: 10.3390/children8020065
|View full text |Cite
|
Sign up to set email alerts
|

“Your Friends Do Matter”: Peer Group Talk in Adolescence and Gender Violence Victimization

Abstract: Research on gender violence has identified as one main component leading to gender violence a dominant socialization process which associates attractiveness to men who show violent behaviors and attitudes, while egalitarian and non-violent men are emptied of attractiveness. This is known as coercive dominant discourse. Starting from the evidence that the peer group is a main context of socialization in adolescence, quantitative data were collected from six classes of secondary education (14–15-year-old adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
1
17
0
Order By: Relevance
“…In this regard, other research has also evidenced the influence of social imaginaries and media messages, often promoted by romantic novels or in women’s erotic literature, that perpetuate this reversal of roles ( Hawley and Hensley, 2009 ). Research also suggests that friendship among girls during their adolescence can either protect them from their peer critics regarding their sexual behavior or lead to double standard reproduction ( Racionero-Plaza et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, other research has also evidenced the influence of social imaginaries and media messages, often promoted by romantic novels or in women’s erotic literature, that perpetuate this reversal of roles ( Hawley and Hensley, 2009 ). Research also suggests that friendship among girls during their adolescence can either protect them from their peer critics regarding their sexual behavior or lead to double standard reproduction ( Racionero-Plaza et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…When Marc worked at a technology company, he remembered one colleague, in particular, representing the DTM model (Roberto). According to Marc, Roberto used to ridicule those men who did not follow his model ( Racionero-Plaza et al, 2021 ) as well as making very derogatory comments toward women. As the company had partners in different European countries, the example provided by Marc refers to a night out of the team after a meeting in Belgium.…”
Section: Resultsmentioning
confidence: 99%
“…Due to this affirmation, dominant boys are learning to use teases for ridiculing others and maintaining their social status. The coercive dominant discourse ( Puigvert and Flecha, 2018 ; Puigvert et al, 2019 ) influences these phenomena, emptying the attractiveness of the OTM men with such comments while reinforcing the link existing between dominant men and desire ( Ruiz-Eugenio et al, 2020a ; Racionero-Plaza et al, 2021 ). In other research, dominant young men are identified with those that are more prone to perpetrate violence against girls ( McCarry, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent analyses show that one of the key components of gender violence victimization among adolescents is the influence on the preferences of adolescent girls to start having an affective-sexual relationship. These preferences are strongly influenced by a coercive discourse that reproduces in the peer group interactions that pressure and push them to have relationships with violent boys ( Racionero-Plaza et al, 2021 ). In this regard, the way of talking to friends and peers can influence preferences, including the different models of masculinity, which is important since each model of masculinity plays a different role in perpetuating or eliminating gender violence ( Flecha et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%